THE EFFECT OF THE MAKE A MATCH COOPERATIVE LEARNING MODEL ASSISTED BY WINGEOM ON STUDENTS’ MATHEMATICAL CONCEPTUAL UNDERSTANDING - Fajrianto, Trian; Putri, Larasati Rizky; Hakim, Lukman El; Aziz, Tian Abdul (Universitas Sembilanbelas November Kolaka, 2025)
This study aims to analyze the effectiveness of Wingeom application in cooperative learning type Make A Match to improve students’ mathematical conceptual understanding. The study was motivated by the low performance of Indonesian students in mathematics as reported in PISA 2022 (OECD, 2022). The research employed a quasi-experimental method with a posttest-only control group design. The sample consisted of 72 eighth-grade students of SMP Negeri 25 Kota Tangerang, divided into an experimental class (using Make A Match with Wingeom) and a control class (conventional learning). The research instrument was an essay test consisting of 11 items that had been validated and tested for reliability. The study provides strong evidence of measuring genuine improvement in students’ mathematical conceptual understanding, as reflected in the significant difference between the experimental group’s mean post-test score of 28.78 and the control group’s mean score of 22.69, supported by a large effect size of 0.893. Therefore, the Wingeom application proved effective in improving students’ mathematical conceptual understanding through cooperative learning type Make A Match.